2014
DOI: 10.1002/app.40791
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterizations of superparamagnetic iron oxide‐embedded poly(2‐hydroxyethyl methacrylate) nanocarriers

Abstract: The present study aims at formulating a novel multifunctional biocompatible superparamagnetic nanoparticles carrier system with homogeneously dispersed magnetic material in solid polymer matrix of poly(2‐hydroxyethyl methacrylate) (PHEMA). The nanocomposites were designed by modified suspension polymerization of 2‐hydroxyethyl methacrylate followed by in situ coprecipitation of iron oxide inside the nanoparticle matrix yielding magnetic PHEMA (mPHEMA) nanocomposites. The so prepared nanocomposites were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…Core/shell structure appeared in Fig. 4c, as a concentrated core and a lighter shell, in which magnetite nanoparticles appeared darker and well dispersed in the whole matrix of nanoparticle (Gupta et al 2014a, b). …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Core/shell structure appeared in Fig. 4c, as a concentrated core and a lighter shell, in which magnetite nanoparticles appeared darker and well dispersed in the whole matrix of nanoparticle (Gupta et al 2014a, b). …”
Section: Resultsmentioning
confidence: 97%
“…Fe 2+ (0.5 M), Fe 3+ (1 M), and Fe 2+ /Fe 3+ (1:2 M), which facilitated an entrapment of different types of iron ions into the casein matrix; one contained only Fe 2+ ions, an other only Fe 3+ ions, and one had both Fe 3+ and Fe 2+ ions. Afterward, these particles were subjected to precipitation of iron oxide in alkaline medium (Gupta et al 2014a, b). Thus, it can be hypothesized that the CNPs containing only Fe 3+ and Fe 2+ ions lead to the formation of maghemite (c-Fe 2 O 3 ) and hematite (a-Fe 2 O 3 ) oxides of iron, whereas CNPs containing both Fe 2+ and Fe 3+ ions in the 1:2 molar ratio preferred the formation of magnetite (Fe 3 O 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 (b, c) shows the corresponding peak of GA besides three new diffraction peaks at 2θ = 30°, 33°, 43° which referred to the existence of a nanocrystalline spinel phase due to (Fe 3 O 4 ) encapsulated in copolymer hydrogel network. The disappearance of 57° and 62° peaks in the diffraction pattern of the nanocomposite is due to covering of (Fe 3 O 4 ) crystallite by crystalline polymer [10]. It has also been observed that the intensity of (Fe 3 O 4 ) peaks has decreased, during its presence in the nanocomposite which is an indication of incorporation within pores of the hydrogel network [33].…”
Section: Fourier-transform Infrared Spectroscopic Analysis (Ft Ir)mentioning
confidence: 99%
“…The reason for superparamagnetic nature of the nanoparticles is due to the very small size of incorporated iron oxide particles which favors the redispersion of magnetic nanoparticles after the external magnetic field is removed [10]. Endoxan loading of (GA/HEMA) copolymer hydrogels and its magnetic nanocomposites The total amount of endoxan adsorbed into dry hydrogels and dry nanocomposites at different initial concentrations of the drug are shown in Fig.…”
Section: Vibrating Sample Magnetometer (Vsm)mentioning
confidence: 99%